Authenticity Manifested: Street Art and Artification - Adam Andrzejewski (Rivista di Estetica, 2017)
The article aims to frame the issue of authenticity regarding street artworks. By introducing and analyzing the concept of artification, which refers to the situation when non-art is modified by art, I argue that street art manifests its authenticity through transforming the space around particular artworks. This transformation amounts to two facts: sanctioning certain practices which change our perception of the urban environment, and creating new aesthetic objects which are art-like.